High-affinity promotor binding of YhaJ mediates a low signal leakage for effective DNT detection - Kim, Myeongbin; Kang, Ryun; Park, Hye Min; Cho, Eun Bi; Lee, Hye Rim; Ryu, Seong Eon (Frontiers in Microbiology, 2025)
The YhaJ transcription factor responds to dinitrophenol (DNT) and its metabolic products. The YhaJ-involving cells have been exploited for whole-cell biosensors of soil-buried landmines. Such biosensors would decrease the damage to personnel who approach landmine fields. By the structure determination of the DNA-binding domain (DBD) of YhaJ and the structure-guided mutagenesis, we found that the mutation increasing the DNA binding affinity decreases the signal leakage in the absence of an effector, resulting in a significant enhancement of the response ratio for the DNT metabolite detection. The decrease in signal leakage explains the LysR-type transcriptional regulators’ (LTTRs’) unique mechanism of signal absence repression by choosing between two different activation binding sites. We showed that the biosensor performance enhancement by the decrease in signal leakage could combine with the previous signal-enhancing mutations. The novel mechanism of performance enhancement of YhaJ shed light on bacterial transcription regulation and the optimization of biosensors that involve the large family of LTTRs.